Using the siliconnitrogenorganic monomers at the synthesis of heterocyclic compounds - A. V. Lega; A. S. Maksimov; A. D. Kirilin (Тонкие химические технологии)
The results of studies reaction transamination of trimethylsilil diethylcarbamate by carbaminosilanes. Shown that siliconnitrogenorganic monomers allows the easy manufacture of heterocyclic compounds. Use of dihydrazines in this reactions leads to organic heterocyclic compounds formation.